A Systematic Literature Review on the Urgency of Imlā’ Learning in Islamic Religious Education: Implications for Religious Literacy and Scholarly Character - Muhammad Firdaus; Ulil Fauziyah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Imlā’ instruction plays a central role in Islamic Religious Education by strengthening Arabic writing accuracy and supporting religious literacy. However, existing studies tend to emphasize its technical outcomes, while the pedagogical, affective, and epistemological dimensions that position imlā’ as a practice shaping scholarly awareness have not been sufficiently synthesized. This study aims to examine the urgency of imlā’ learning and its contribution to learners’ academic competence and scholarly character through a Systematic Literature Review (SLR). Following PRISMA guidelines, this review analyzed 21 peer-reviewed studies published between 2015 and 2025. Data were collected from Scopus, SINTA, DOAJ, and Google Scholar and systematically analyzed to identify research designs, imlā’ methods, and learning outcomes. The findings indicate that most studies consistently report positive effects of imlā’ instruction on Arabic writing accuracy, including improved letter formation, orthographic precision, and reduced imlā’iyyah errors. Several studies also highlight affective benefits, such as increased focus, discipline, and learning responsibility, while a smaller number of studies address persistent challenges in academic writing accuracy at higher education levels. The integration of digital media remains limited and functions primarily as a supportive tool rather than a replacement for manual writing practice. Overall, the review confirms that imlā’ instruction is not merely a technical exercise but a foundational pedagogical practice that contributes to religious literacy, disciplined learning habits, and scholarly character.